A meta-analysis on the relationship of eNOS 4b/a polymorphism and diabetic nephropathy susceptibility. (November 2014) - Zeng, Rong; Duan, Lei; Sun, Lina; Kong, Yuke; Wu, Xiaolu; Wang, Ya; Xin, Gang; Yang, Kehu
Abstract To clarify the effect of nitric oxide synthase (NOS) type III 4b/a polymorphism on the susceptibility to diabetic nephropathy (DN) by meta-analysis, we performed a computerized search of PubMed, EMBASE, Chinese BioMedical Literature Database, China Science and Technology Journal Database, Chinese Journal Full-text Database and WanFang to identity case–control studies on relationship between NOS type III 4b/a polymorphism and the susceptibility to DN. Statistic analysis and heterogeneity test were conducted by StataSE12. The meta-analysis involved 26 studies for DN comparing with diabetes mellitus (DM) and 15 studies for DN comparing with healthy persons, which provided 6144/4900 cases/controls and 2134/2348 cases/controls, respectively. Moderate heterogeneity was found among including studies. The qualities of half studies are low. Meta-analysis derived a significant association between the NOS type III 4b/a and the risk of developing DN in Asian population. The sensitivity analysis (exclusion of studies not in Hardy–Weinberg equilibrium) produced non-significant changes. Compared with diabetes patients, the pre-allele model produced certain association in global populations [odds ratio (OR) = 1.26, 95% confidence interval (95% CI): 1.10–1.45], significant association in Asian population (OR = 1.51, 95% CI: 1.13–2.01) and certain association in type 2 DM patients (OR = 1.29, 95% CI: 1.09–1.54). Only in the dominant model, the funnel plot and Egger's test provided evidence of publication bias (p = 0.024). Overall, although there is some evidence of association between NOS type III 4b/a polymorphism and DN in Asian population, the more reliable findings need further and more rigorous, prospective and high-quality studies.